NEW GALL MIDGES (DIPTERA, CECIDOMYIIDAE) FROM THE ROVNO AMBER: SUBFAMILY LESTREMIINAE, TRIBES STROBLIELLINI AND CAMPYLOMYZINI; SUBFAMILY PORRICONDYLINAE, TRIBES DIADOCIDIINI AND ASYNAPTINI - Fedotova Z.A.; Perkovsky E.E. (My University, 2004)
Seven new species of gall midges belonging to the genera Strobliella, Campylomyza, Neurolyga, Diadocidia , and Camptomyia are described from the Eocene Rovno amber.
Keywords: Cenozoic::Paleogene::Eocene; Кайнозой::Палеоген::Эоцен